Analisis Pengaruh Stres Kerja, Kompensasi, dan Lingkungan Kerja terhadap Turnover Intention (Studi Kasus pada PT. Sukses Ekspor Indonesia) - Musyaffa, Muhammad Faris; Mansur, Mochammad (Jurnal EMT KITA, 2026)
This study aims to analyze the effect of job stress, compensation, and work environment on turnover intention among employees of PT. Sukses Ekspor Indonesia. The study employs a quantitative approach using a causal method. Data were collected through the distribution of questionnaires to all employees of PT. Sukses Ekspor Indonesia, totaling 37 respondents, using a saturated sampling technique. The data were analyzed using multiple linear regression with SPSS 27 as the analytical tool. The results indicate that job stress has a positive and significant effect on turnover intention, meaning that the higher the level of job stress experienced by employees, the greater their tendency to leave the company. Compensation has a negative and significant effect on turnover intention, indicating that fair and adequate compensation can reduce employees’ intention to leave the company. In addition, the work environment also has a negative and significant effect on turnover intention. Based on these findings, companies are expected to manage job stress more effectively, improve compensation systems, and create a more conducive work environment to reduce employees’ turnover intention.